Factors influencing continuity in online education: a replication study in the Ecuadorian university context - Carbo Vélez, Carlos; González Vázquez, Karina Yuleisy; Cedillo Pucha, María Natalia; Pacheco Olea, Fernando; Valenzuela Cobos, Juan (Frontiers in Education, 2026)
The rapid development of digital technologies has established e-learning as an essential component of modern higher education. In Ecuador, the expansion of online education has created new challenges in terms of student retention and the sustainability of virtual programs. The objective of this study was to identify the factors that influence Ecuadorian university students’ intention to continue in virtual environments and to replicate and validate a model previously applied in China. For the empirical analysis, a structured survey was administered to 477 students enrolled in virtual programs at the State University of Milagro during May and June 2025. Data processing was performed using structural equation modeling (SEM), based on the information systems success model and service quality theory. The measurement instrument showed adequate reliability and convergent validity (Cronbach’s α = 0.872; CR > 0.87; √AVE > 0.75). The results indicate that interactions particularly teacher-student and peer relationships have a significant effect on perceived value and, consequently, on intention to continue, while service quality and course quality play a lesser role in the Ecuadorian context. Overall, the results replicate several patterns described in the Chinese study, although contextual differences suggest that the online education experience in Ecuador is more strongly determined by sociocultural and relational factors. Practical implications include strengthening pedagogical interaction strategies and promoting student-centered methodologies. Future studies should incorporate longitudinal and mixed-method approaches to deepen the understanding of perceived value and continuity of online learning in Latin America.